Groups with the Same Prime Graph as the Simple Group D_n (5) - Babai, A.; Khosravi, B. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
Let G be a finite group. The prime graph of G is denoted by Γ(G). Let G be a finite group such that Γ(G) = Γ(D_n (5)), where n ≥ 6. In the paper, as the main result, we show that if n is odd, then G is recognizable by the prime graph and if n is even, then G is quasirecognizable by the prime graph.